The occurrence of flexion-relaxation phenomenon in elite cyclists during trunk forward bending - Hashem boroojerdi, M.; Rahimi, A.; Roostayi, M. M.; Talebian Moghaddam, S.; Yousefi, M.; Norouzi, M.; Akbarzadeh Baghban, A. (Sports Biomechanics, 2022)
Flexion-relaxation phenomenon (FRP) is a well-known phenomenon in spinal extensor muscles. According to the literature, prolonged flexed posture leads to creep phenomenon and affects the active and passive neuromuscular control of the spinal column. The purpose of this study was to investigate FRP occurrence in elite cyclists that prolonged flexion posture is an integral part of their professional life. Their muscles` contraction pattern during forward bending was also compared. Electromyography (EMG) was recorded during flexion and extension from standing position in thoracic erector spinae (TES), lumbar erector spinae (LES) and gluteus maximus (Gluteus max) in 15 healthy male elite cyclists. In addition, the kinematic data related to the trunk angles were simultaneously recorded by a motion analysis system. Two-way ANOVA was used to assess the effects of muscle group and direction of movement on maximum amplitude of EMG activity. Among 15 cyclists, FRP was detectable in 60%, 87% and 73% of the participants in TES, LES and Gluteus max, respectively, and happened between 74% and 82% of the trunk flexion. There was no statistically significant difference in onset and offset of muscles FRP. Despite prolong hyper kyphotic posture, FRP was identifiable in TES, LES and Gluteus max muscles of elite cyclists.